Paper - Matthews, Samantha (Romanticism on the Net)

(untitled) (Université de Montréal, 2023)
Thomas Carlyle characterised pre-Revolutionary France as “The Paper Age,” where paper signifies a flimsy and fraudulent culture of inflated ideas and depreciated money. Yet paper was also the substantial vehicle of Romantic literary and intellectual endeavour and the circulation of ideas—a ubiquitous, multifarious medium and powerful agent of cultural change across Romantic Europe. Paper means books, magazines, manuscripts, letters, but also wallcoverings, wrappings, papier maché objets d’art, and waste. This essay explores the multivalencies of Romantic paper: at once fragile, vulnerable, and ephemeral (the single sheet) and resilient, flexible, and enduring (the bound book); both high culture (Wordsworth’s The Excursion) and high prestige (Coleridge’s unique Malta notebook) but also low culture (playbills) and low prestige (manufactured from rags). Shifting attention from the inky message to the paper medium, and drawing on technological, economic, ecological, regional, and labour contexts of paper manufacture, distribution, use, and reuse, this article aims to theorise and apprehend anew a tactile and affectively loaded Romantic material that can be invisible and elusive in its portability, transformability, and pervasiveness.